2000
DOI: 10.1007/s003840000212
|View full text |Cite
|
Sign up to set email alerts
|

The role of obesity on the recurrence of pilonidal sinus disease in patients, who were treated by excision and Limberg flap transposition

Abstract: Recurrence of pilonidal sinus disease after surgical intervention is not a very rare problem although sophisticated reconstruction procedures have been developed. Recurrence is thought to be related to the anatomical status of the patients, i.e., depth of the intergluteal groove. Obese patients have deeper intergluteal grooves. The aim of this study was to use body mass index (BMI) as an objective indicator of obesity to determine whether there is a relationship between BMI and recurrence of pilonidal sinus di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 6 publications
1
50
0
9
Order By: Relevance
“…None of the publications related to phenolization has considered this issue when selecting patients. Similarly, obesity has been reported as a risk factor in patients with PD (33,35). This particular patient group with deep intergluteal sulcus or obesity might not benefit from phenol application.…”
Section: Patient Featuresmentioning
confidence: 78%
“…None of the publications related to phenolization has considered this issue when selecting patients. Similarly, obesity has been reported as a risk factor in patients with PD (33,35). This particular patient group with deep intergluteal sulcus or obesity might not benefit from phenol application.…”
Section: Patient Featuresmentioning
confidence: 78%
“…Cubukcu et al had found that obese patients with high body mass index had a higher risk of recurrence of PNS after surgical intervention (60). Nevertheless, Cubukcu et al in another study have found that obesity alone is not an important factor in the etiology of PNS (61).…”
Section: Role Of Laser Hair Removal (Lhr)mentioning
confidence: 99%
“…Ayrıca direne edilmemesi halinde yaygın doku hasarı ile birlikte sepsis odağı oluşturabilmekte ve rekürren apseler ile başvuran hastalarda anal kanala ve perianal bölgeye uzanım görülebilmektedir. 6,7 Çalışmamızda sakrokoksigeal bölgede akut pilonidal apse ile başvuran ve Limberg flep uyguladığımız hastaların geç dönem sonuçları değerlendirilmiştir. 16 Garg ve ark.…”
Section: Introductionunclassified